MASA PERTUMBUHAN DAN PERKEMBANGAN PENDIDIKAN ISLAM - Ruwi Anandha Arriya Rahman; Vihas Ariski Sunadi; Khalil Asyhuda; Ikhsan Alramadhan; Jadu Kurniawan; Sriliza (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study examines the development of Islamic education from the Prophet’s era to the modern period, focusing on concepts, practices, and learning challenges. The research uses a literature review approach, relying solely on books as sources to describe the understanding of worship values, morals, and religious character in children. The results show that Islamic education continuously adapts through classical madrasas, pesantren, and modern technology integration. Moral values remain the main focus despite evolving teaching methods and media. This study provides insights for teachers, researchers, and policymakers to develop relevant and inspiring Islamic education